Inflammatory myofibroblastic tumor of the lung in pregnancy mimicking carcinoid tumor - Maturu, Venkata Nagarjuna (Lung India, 2016)
Inflammatory myofibroblastic tumors (IMT) are uncommon neoplasms of the lung in adults. They constitute less than 1% of all lung neoplasms and usually present as parenchymal masses. Diagnosis requires a high index of suspicion. They are characterized by spindle-shaped tumor cells (fibroblasts/myofibroblasts) in a background of lymphoplasmacytic infiltrate. About 50% of the tumors harbor an ALK gene rearrangement. They have to be differentiated from inflammatory pseudotumors (IPT), which show increased number of IgG4 plasma cells on immunostaining and are negative for anaplastic lymphoma kinase (ALK) protein. Herein, we present a case of a 28-year old female who presented with hemoptysis and was diagnosed with an IMT of lung in the first trimester of pregnancy. We have not only reviewed the occurrence of IMT during pregnancy but also discuss the management options for IMT during pregnancy.